Penggunaan Metode Drill Pada Pelaksanaan Ekstrakurikuler Musik Tradisional di SMP Angkasa Lanud Sutan Sjahrir Padang - Puspa, Puspa Agustin; Irdhan Epria Darma Putra (Universitas Negeri Padang, 2023)
The purpose of this study to find out how to use the drill method in the implementation of traditional music extracurriculars at SMP Angkasa Lanud Sutan Sjahrir Padang. The learning method used by the trainer is the drill method. In this study used descriptive analytical method by utilizing qualitative data. The object of this study were students who took part in extracurricular activities of traditional music at SMP Angkasa Lanud Sutan Sjahrir Padang. Data collection techniques will be carried out in the form of observation, interviews, literature study, document study. Data analysis uses primary data and secondary data. The results showed that in implementing the drill method, it can improve students' abilities and understanding in playing traditional musical instruments at Angkasa Junior High School Sutan Sjahrir Padang Field. The use of various tempos from fast to slow can help students play pasambahan songs. The drill method used in the implementation of traditional music extracurricular activities makes students able to understand and master the song material given